PENGARUH PENERAPAN MODEL PEMBELAJARAN INSIDE OUTSIDE CIRCLE TERHADAP HASIL BELAJAR SISWA KELAS X SMAN 1 SUNGAI RAYA KABUPATEN KUBU RAYA - Emusti Rivasintha Marjito; Kiki Rizki (Khazanah Pendidikan, 2015)
The aim in this study was to determine the effect of the application of learning models inside outside circle of the student learning outcomes material early life of the Indonesian people for class X State Senior High School 1 Sungai Raya Kubu Raya. The independent variable in this study is a learning model Inside Outside Circle. The dependent variable in this research is student learning outcomes. The hypothesis of this study is the application of learning models are the effect of Inside Outside Circle on student learning outcomes material early life of the Indonesian people for class X State Senior High School 1 Sungai Raya Kubu Raya. This is a form of preexperimental research design. The design used in this study is one group pre-test post-test design. The population in this study were students of class X State Senior High School 1 Sungai Raya Kubu Raya 2014-2015 academic year of six classes. Techniques used in collecting the data is the measurement data collection tool is a test student learning outcomes. Results showed the conclusions: (1) The average value of student learning outcomes before using model Inside Outside Circle material early life of the Indonesian people for class X State Senior High School 1 Sungai Raya Kubu Raya was 63 with a standard deviation of 11, 10. (2) The average value of student learning outcomes after using model material Inside Outside Circle early life of the Indonesian people for class X State Senior High School 1 Sungai Raya Kubu Raya is 77 with a standard deviation of 9.28. (3) There is the effect of the application of learning models Inside Outside Circle on student learning outcomes material early life of the Indonesian people for class X State Senior High School 1 Sungai Raya Kubu Raya. Keywords: outside circle model, history learning